2014
DOI: 10.1063/1.4886120
|View full text |Cite
|
Sign up to set email alerts
|

A widely tunable 10-μm quantum cascade laser phase-locked to a state-of-the-art mid-infrared reference for precision molecular spectroscopy

Abstract: We report the coherent phase-locking of a quantum cascade laser (QCL) at 10-µm to the secondary frequency standard of this spectral region, a CO 2 laser stabilized on a saturated absorption line of OsO 4 . The stability and accuracy of the standard are transferred to the QCL resulting in a line width of the order of 10 Hz, and leading to our knowledge to the narrowest QCL to date. The locked QCL is then used to perform absorption spectroscopy spanning 6 GHz of NH 3 and methyltrioxorhenium, two species of inter… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
43
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 45 publications
(44 citation statements)
references
References 40 publications
0
43
0
Order By: Relevance
“…Novel applications of QCLs in very high-resolution spectroscopy and optical metrology have emerged in the last years, in particular in combination with optical frequency combs [2][3][4][5], which are generally more demanding in terms of low frequency-noise and nar-row spectral linewidth. QCLs have the potential to achieve very narrow linewidths with an intrinsic value of a few hundreds hertz only [6,7] resulting from their close-to-zero Henry's linewidth enhancement factor [8]. However, a narrow linewidth is generally not achieved in practice in freerunning QCLs as a result of the presence of undesired noise that compromises their spectral properties.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Novel applications of QCLs in very high-resolution spectroscopy and optical metrology have emerged in the last years, in particular in combination with optical frequency combs [2][3][4][5], which are generally more demanding in terms of low frequency-noise and nar-row spectral linewidth. QCLs have the potential to achieve very narrow linewidths with an intrinsic value of a few hundreds hertz only [6,7] resulting from their close-to-zero Henry's linewidth enhancement factor [8]. However, a narrow linewidth is generally not achieved in practice in freerunning QCLs as a result of the presence of undesired noise that compromises their spectral properties.…”
Section: Introductionmentioning
confidence: 99%
“…Hence, the char-acterization and understanding of the origin of frequency noise spectrum of free-running QCLs gained a significant interest in the recent years. A few research groups reported experimental frequency noise spectra for QCLs produced by different manufacturers and operated at temperatures ranging from cryogenic [7,9] up to room temperature [6,10,11]. Significantly different levels of noise have been observed in the considered QCLs, leading to linewidths in the range of sub-100 kHz [6] to many megahertz [7].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Climate modeling and global change research programs are setting unprecedented accuracy targets in gas-sensing missions for atmospheric CO 2 and other greenhouse gases [1]. The desired uncertainty can only be reached by making high quality measurements of spectroscopic parameters (including pressure broadening coefficients and line intensity factors) using well-designed and characterized experiments [2][3][4][5]. Similarly, the interpretation of spectra of astrophysical and planetary interest needs a precise knowledge of line-shape parametres and current databases require further improvements [6,7].…”
Section: Introductionmentioning
confidence: 99%
“…The free-running linewidth on the timescale of 1 s is typically on the order of 1 MHz and has been the subject of several studies [2,11]. Linewidth narrowing, alongside absolute frequency stabilization and finally absolute frequency measurement, are therefore important tasks for rendering QCLs usable for high-resolution spectroscopy.It has already been shown that the QCL linewidth can be dramatically reduced, by locking to a reference cavity [10], by phase-locking to a narrow-linewidth CO 2 reference laser, reaching less than 10 Hz relative linewidth [9], or by phase-locking to the DFG wave generated from two near-IR cw lasers [5]. This latter approach however limits the spectral coverage of the QCL, since it relies on particular reference lasers.…”
mentioning
confidence: 99%